Professional Organization as A Place for Strengthening Teachers’ Competency in The Disruption Era - Riskawati Riskawati; Sapriya Sapriya; Iim Siti Masyitoh (AIBPM Publisher, 2020)
Disruption is characterized by the use of technology in almost all fields including Education. The biggest challenge for teachers is to mastery the technology. This study is to determine the role of the Professional Teacher Organization in strengthening Teachers’ Competence in the disruption era as mandated in the Law number 14/2005 about Teacher and Lecturer. The Qualitative method used shows that the digital competency is the aspect to be developed by the teacher through various trainings conducted by the Professional Teacher Organization. The role of this organization is to design the work programs from the National level to the regions. Therefore, it is necessary to strengthen the organizational leadership, professionalism, and organizational commitment and cooperation with government and non-government institutions.